Drug use prevalence among students of universities of medical sciences in Tehran - Farhad Taremian; Jafar Bolhari; Hamid Peyravi; Ali Asgari (Drug Control Headquarters, Research and Education Office, 2014)
Objective: This study was aimed to determine the prevalence of drug use among students of universities of Medical Sciences in Tehran. Method: Four thousands of medical students (both sexes) in academic year 1388-89 in different level of education, B.A., M.Sc. and Ph.D. were selected by random stratified sampling method. These students were selected from Iran, Tehran and Shahid Beheshti Universities of Medical Sciences considering their sex and level of education. We used drug use prevalence questionnaire. Findings: The most prevalent drug of abuse in life time period was qalyan (classical pipe), followed by cigarette, and alcohol. The least frequent drug of abuse was Shisheh, followed by heroine krack. As we expected, drugs morphine, ritalin and tramadol were placed in forth, fifth and sixth of prevalent drugs. Use of different substances was significantly more prevalent in male students. Conclusion: Using soft drugs (qalyan, cigarette and alcohol) was more prevalent than hard drugs (hashish, taryak, heroine kerack) among Universities Medical Sciences of Tehran. Similar to drug use pattern in society, use of all of drugs were more prevalent in male students. We should pay special attention to use of drugs such as tramadol, ritalin, petedin and morphine.